(3GdCMcGe aj CUhd GdCMcGes - (3Ydj Hf CHj Ydj Hf eMeO, CHh GdMSf GdeYQha HSja GdOjf GdGeOjs ((3eMehO Hf YHO GdeDef Hf eMehO GdhGSWi s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCadGc heOjQgG hHYO aEfg deG cGf GdCMcGe GdTQYjI hGdbVGjG GdabgjI GdbGYOI GdChdi ai JMbjb eaghe CUhd Gdabg s
(3BNQgG (B:s
(3hbO jJTYH ef JbGHd gPg GdJQLjMGJ JQLjMGJ CNQi cKjQI hgPG BNQ eG CQOfGg hfgGjI eG QJHfGg Efc eLjH GdOYhGJ heajV GdNjQGJ s
(3aQZ ef JCjag SfI (B620s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs